Electrosynthetic reduction of 1-iodoadamantane forming 1,1'-biadamantane and adamantane in aprotic solvents: insonation switches the mechanism from dimerisation to exclusive monomer formation. - Paddon, C; Bhatti, F; Donohoe, T; Compton, R (2007)
The combination of ultrasound and electrochemistry -sonoelectrochemistry can produce a variety of effects within an electrochemical system including enhanced mass transport, in situ cleaning of an electrode surface, diminution of the diffusion layer, and possible induction of new reactions by sonochemical enhancement of follow-up reactions post-electron transfer. Herein, we show that ultrasound provides a useful extra dimension to electrosynthesis via a switch in the sonoelectroorganic mechanism in which dimerisation is disfavoured by virtue of convective mixing promoted by insonation. Under 'normal' voltammetric conditions the reduction of 1-iodoadamantane at a silver cathode in tetrahydrofuran (THF) and acetonitrile (ACN) involves a single electron forming a mixture of monomeric and dimeric products; 58%/THF, 50%/ACN adamantane and 39%/THF, 50%/ACN 1,1'-biadamantane, respectively. However, under the conditions of insonation using a 10 kHz transducer, a single product is formed exclusively; 93%/THF, 96%/ACN adamantane. The effect of insonation upon the voltammetry at a silver macroelectrode is shown and compared to that under silent conditions. In addition, the previously observed characteristic series of oxidation and adsorption peaks following reduction of 1-iodoadamantane are reduced in magnitude under insonation. Overall, this work shows that the effect of insonation can switch the mechanism of follow-up chemical processes - favoring the formation of a monomer.